Clinicopathologic characteristics of ovarian clear cell carcinoma in the background of endometrioma: a surveillance strategy for an early detection of malignant transformation in patients with asymptomatic endometrioma - Joo-Hyuk Son; Seokyoung Yoon; Seokyung Kim; Tae-Wook Kong; Jiheum Paek; Suk-Joon Chang; Hee-Sug Ryu (Korean Society of Obstetrics and Gynecology, 2019)
ObjectiveThis study aimed to analyze the clinical features of clear cell carcinoma in relation to endometriosis and to determine an appropriate surveillance strategy for the early detection of malignant transformation of endometrioma in asymptomatic patients.MethodsWe retrospectively reviewed the clinicopathologic data of 50 patients with ovarian clear cell carcinoma. Clinicopathologic characteristics, treatment outcomes, and the association between endometriosis and the risk of malignant transformation were analyzed.ResultsTen (20%) patients had been diagnosed with endometrioma before the diagnosis of clear cell carcinoma. The median period from the diagnosis of endometrioma to clear cell carcinoma diagnosis was 50 months (range, 12-213 months). After complete staging surgery, histological confirmation of endometriosis was possible in 35 (70%) patients. Of the 50 patients, 39 (78%) had not undergone any gynecologic surveillance until the onset of symptoms, at which time many of them presented with a rapidly growing pelvic mass (median 10 cm, range 4.6-25 cm). With the exception of 2 patients, all cancer diagnoses were made when the patients were in their late thirties, and median tumor size was found to increase along with age. Asymptomatic patients (n=11) who had regular gynecologic examinations were found to have a relatively smaller tumor size, lesser extent of tumor spread, and lower recurrence rate (P=0.011, 0.283, and 0.064, respectively). The presence of endometriosis was not related to the prognosis.ConclusionConsidering the duration of malignant transformation and the timing of cancer diagnosis, active surveillance might be considered from the age of the mid-thirties, with at least a 1-year interval, in patients with asymptomatic endometrioma.